Venous thromboembolism - An unusual case of treatment resistance (Indian Journal of Case Reports, 2020)
Nephrotic syndrome (NS) is associated with a hypercoagulable state and hence a serious risk of thromboembolism. Diagnostic and anticoagulation-related management strategies are controversial in NS. We report the case of a 32-year-old young male presenting with deep vein thrombosis (DVT) WHO on evaluation, was diagnosed with NS. Despite several days of standard medical therapy with low-molecular-weight heparin and warfarin and surgical intervention, clinical response was lacking. However, a dramatic improvement was observed after initiation of rivaroxaban therapy, with complete resolution of DVT in 2 weeks.